Defining oligometastatic state in uro-oncological cancers - Fazekas, Tamás; Miszczyk, Marcin; Matsukawa, Akihiro; Nyirády, Péter; Shariat, Shahrokh F; Rajwa, Pawel (Current opinion in urology, 2024)
PURPOSE OF REVIEW: Oligometastatic tumors illustrate a distinct state between localized and systematic disease and might harbor unique biologic features. Moreover, these tumors represent a different clinical entity, with a potential of long-term disease control or even cure, therefore they receive growing attention in the field of urologic oncology. RECENT FINDINGS: Currently, there is no consensus on the definition of oligometastatic prostate cancer, most experts limit it to a maximum of three to five lesions and involvement of no more than two organs, excluding visceral metastases. Quality data on oligometastatic bladder cancer is scarce, however, a consensus of experts defined it as a maximum of three metastatic lesions, either resectable or suitable for stereotactic therapy, without restrictions to the number of organs involved. As for kidney cancer, a maximum number of five metastases, without limitations to the location are defined as oligometastatic, with an important implication of timing of developing metastases since diagnosis of the primary tumor. SUMMARY: Defining oligometastatic state among urological tumors reflecting their distinct biological and clinical behavior is crucial to establish a sound framework for future clinical trials, and to facilitate guideline and policy formulation for improved patient care. Advancements in molecular imaging are expected to transform the field of oligometastatic urologic tumors in the future.
Keywords: nádory močového měchýře; nádory ledvin; Neoplasm Metastasis; Kidney Neoplasms; Male; Urinary Bladder Neoplasms; Prostatic Neoplasms; lidé; urologické nádory; metastázy nádorů; mužské pohlaví; Urologic Neoplasms; Humans; nádory prostaty